The Temple of Jerusale m from Moses to the Messiah : in honor of Professor Louis H. Feldman - Feldman, Louis H.; Fine, Steven. (The Brill Reference Library of Judaism, 2011)
The Temple of Jerusalem: From Moses to the Messiah brings together an interdisciplinary and broad-ranging international community of scholars to discuss aspects of the history and continued life of the Jerusalem Temple in Western culture, from biblical times to the present. This volume is the fruit of the inaugural conference of the Yeshiva University Center for Israel Studies, which convened in New York City on May 11-12, 2008 and honors Professor Louis H. Feldman, Abraham Wouk Family Professor of Classics and Literature at Yeshiva University. Feldman is the doyen of modern scholarship on Judaism in the Greco-Roman period, focusing on the writings of Flavius Josephus. A beloved mentor to generations of Yeshiva University students and of scholars across the globe, Professor Feldman has taught at YU since 1955. \'The articles are consistently of high quality. This book is highly recommended for any academic collection in Jewish studies.\' Jim Rosenbloom, Judaica Librarian, Brandeis University; President, Association of Jewish Libraries